Asuhan Keperawatan Pada Klien dengan Post Operasi Hernia Inguinalis Lateralis di RSUD Sukoharjo - Cahyo, Bagus Wisnu Tri; , Okti Sri Purwanti, S.Kep., Ns., M.Kep., Ns.Sp.Kep.M.B (2015)
Background: Inguinal hernias are more common in men than women because when the content of the testicles in the abdomen down. If it does not close perfectly result into the path hernia. Objective: To study the nursing care to clients with post lateral inguinal hernia operation which include assessment, intervention, implementation, and evaluation. Results: After 3x24 hour nursing care for the results obtained, the client pain complaints decreased from a scale of 3 to 1, increased daily activity, there is no sign of infection risk. Conclusion: The issue is resolved for the diagnosis of acute pain and impaired mobility. As for the risk of infection is resolved and the necessary follow up portion that requires cooperation with the patient, family, and health care team.